Structural properties of close II₁ factors - Cameron, J; Christensen, E; Sinclair, A; Smith, R; White, S; Wiggins, A (Mathematical Institutes of the Universität Münster, 2017)
We show that a number of key structural properties transfer between sufficiently close II₁ factors, including solidity, strong solidity, uniqueness of Cartan masas and property Γ. We also examine II₁ factors close to tensor product factors, showing that such factors also factorise as a tensor product in a fashion close to the original.